2020
DOI: 10.3390/children7100173
|View full text |Cite
|
Sign up to set email alerts
|

Good Subjective Outcomes, Stable Knee and High Return to Sport after Tibial Eminence Avulsion Fracture in Children

Abstract: Avulsion fracture of the tibial spine (TSA) is uncommon in children, although its incidence is increasing with the earlier practice of competitive sport activities. This study aims to report mid to long term outcomes in children who sustained a TSA, with a special focus on a return to sport activities. Skeletally immature patients with a TSA, treated in two orthopedic hospitals, were evaluated for range of motion and knee laxity using KT1000, KiRA and Rolimeter. The pediatric International Knee Documentation C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Patients who underwent reoperation had lower IKDC scores but experienced no further impediments to returning to their previous levels of play in sports. In the literature, pain and fear of reinjury have been the most common patient-reported reasons for failing to return to preinjury-level play, 30 which is consistent with the findings of this research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients who underwent reoperation had lower IKDC scores but experienced no further impediments to returning to their previous levels of play in sports. In the literature, pain and fear of reinjury have been the most common patient-reported reasons for failing to return to preinjury-level play, 30 which is consistent with the findings of this research.…”
Section: Discussionsupporting
confidence: 90%
“…Most patients recover well after a TSA fracture. 7,23,26-28, 30 Stallone et al 30 reported good outcomes after operative and nonoperative care, although their study population was small and the majority of the participants were treated nonoperatively (23 vs 16). Furthermore, 78% of their patients returned to their previous levels of play in sports, and the mean Pedi-IKDC score was 96.4 ± 5.7.…”
Section: Discussionmentioning
confidence: 99%
“…However, immobilization can cause pathological changes in the body's joint capsule, ligaments, muscles, and other tissues in terms of morphological structure, biochemistry, and biochemical mechanics and ultimately affect the function of joints and limbs [ 13 ]. In order to avoid knee joint dysfunction, a comprehensive treatment based on early functional activities has to be adopted [ 14 ].…”
Section: Discussionmentioning
confidence: 99%